Eimeria atlapetesi nom. nov., a replacement name for Eimeria pileata Soriano-Vargas et al., 2015 (Apicomplexa: Eimeriidae), preoccupied by Eimeria pileata Straneva and Kelley, 1979 (Apicomplexa: Eimeriidae), with observations on histopathology and phylogenetic analysis - Soriano-Vargas, Edgardo; Salgado-Miranda, Celene; Zepeda-Velázquez, Andrea Paloma; Medina, Juan Pablo; Janczur, Mariusz Krzysztof; González-Gómez, Maricruz; Flores-Valle, Izanami Tereira; Berto, Bruno Pereira; Lopes, Carlos Wilson Gomes (Zootaxa, 2017)
Eimeria pileata Soriano-Vargas, Medina, Salgado-Miranda, García-Conejo, Galindo-Sánchez, Janczur, Berto and Lopes, 2015 is a junior homonym of Eimeria pileata Straneva and Kelley, 1979 and needs to be replaced. This coccidium was described from a rufous-capped brush finch Atlapetes pileatus Wagler in the Nevado de Toluca Natural Protected Area, Mexico. Thus, to maintain the original intent of the specific epithet derived from the scientific name of the type-host, the name Eimeria atlapetesi nom. nov. is proposed as a replacement name. Additionally, the current work reports another rufous-capped brush finch A. pileatus parasitized by E. atlapetesi in co-infection with an Isospora sp., providing observations of histopathology and phylogenetic analysis of 18S ribosomal RNA (rRNA) gene from E. atlapetesi. Endogenous forms of E. atlapetesi and Isospora sp. were observed in intestinal sections. Few oocysts of Isospora sp. were observed; therefore they were not morphologically or molecularly identified. In return, E. atlapetesi was identified and it was phylogenetically close to Eimeria dispersa Tyzzer, 1929 from the domestic turkey Meleagris gallopavo Linnaeus.